Nutritional Interventions and Management Strategies in Pediatric Food Allergies: A Review - Javed, Tehseen; Farheen, Nafisa; W, Anitha; N B, Geetha; C, Geetha, (Journal of Neonatal Surgery, 2025)
The prevalence of childhood food allergies is increasing in both developed and developing countries, posing a significant public health challenge. This review aims to synthesize current evidence on the prevention and management of food allergies, with a particular focus on the role of nutritional components and dietary practices in supporting immune system development and function. Key nutrients such as essential fatty acids, zinc, and vitamin D are believed to enhance the body’s anti-inflammatory and antioxidative defenses, thereby promoting immunological tolerance. Moreover, emerging research highlights the potential of prebiotics and probiotics in modulating gut microbiota and fostering a tolerogenic immune environment. These insights have prompted a critical reassessment of the traditional avoidance-based dietary strategies. Recent findings suggest that early exposure to a diverse range of dietary antigens during infancy may reduce the risk of allergic sensitization by supporting the maturation of the immune system. Consequently, both therapeutic and preventive interventions must be personalized, accounting for individual nutritional needs and allergic risk profiles.